Documenting the Voices of Women Conference in Weimar 2024: Blueprint of a Zine - Zacharias, Constanze (Septentrio Creative, 2026)
The blueprint of the zine documents results from the ‘Voices of Women’ conference 2024 in Weimar organized by researchers, artists and students from Stavanger, Tromsø, Weimar and Groningen. The zine is an innovative and artistic way for conference participants to store their notes and reactions. It breaks with traditional practices of academic engagement and dissemination of knowledge. Through its flexible and spontaneous form, it enables to communicate ideas expressed by researchers in multimodal ways. At one glance, a wide range of associations and topics are presented with the space to add a comment, a conclusion, or a follow-up question by the keeper of the Zine.